New Trend In New Normal, Factors Influencing Continuance Intention to Use Video Conferencing - Rahmat Hidayat (Jurnal Ilmiah Poli Bisnis, 2020)
Work from home to prevent the spread of covid-19 drive the increase of use video conferencing at work. Although now entering the new normal era, the reuse of video conferencing will continue to increase. Working using video conferencing has become a new trend. But the lack of literature and research related to video conferencing makes a lack of understanding of consumer behavior regarding the continuance intention of video conferencing. This study proposed a model which is a modification from Theory Aceptance Model (TAM), that has benn proven be able to explain consumers behavior in adoption technology. Data collected from 219 respondents, then analyzed with partial least square method using SmartPLS. The results show that perceived usefulness, perceived ease of use, and social influence have a positive and significant influence on continuance intention of video conferencing. While perceived enjoyment only has a positive and significant effect indirectly, and facilitating conditions do not have a significant effect on continuance intention. The results of this study contribute to understanding consumer behavior continuance intention of video conferencing.